Fc-effector functional antibody assays for SARS-CoV-2 variants of concern - Chen, Xuemin; Li, Grace; Ciric, Caroline; Gibson, Theda; Anderson, Larry J.; Rostad, Christina A. (Frontiers in Immunology, 2025)
BackgroundThe Fc regions of antibodies mediate important effector cell functions such as antibody-dependent cellular cytotoxicity (ADCC), antibody-dependent cellular phagocytosis (ADCP), antibody-dependent neutrophil phagocytosis (ADNP), and complement-dependent cytotoxicity (CDC). These functions enhance immune defense and infected cell clearance. This study evaluated the effect COVID-19 XBB.1.5 booster vaccination on Fc-effector antibody responses to SARS-CoV-2.MethodsWe developed four assays to evaluate the Fc-effector functions of SARS-CoV-2 antibodies. ADCC and CDC assays utilized stably transfected luciferase-based target cell lines expressing SARS-CoV-2 spike variants (Ancestral, Wu-1 Omicron XBB.1.5, and EG.5) to measure antibody-mediated lysis by effector cells. ADCP and ADNP were assessed by flow cytometry to measure phagocytosis of fluorescently labeled virus-like particles that display SARS-CoV-2 variant spike proteins. Serum samples from 20 healthy adult volunteers pre- and post-monovalent XBB.1.5 COVID-19 vaccine were analyzed for pseudovirus neutralizing and Fc-effector antibodies.ResultsPrior to administration of the COVID-19 XBB.1.5 booster vaccination, cross-neutralizing antibodies against XBB.1.5 and EG.5 variants were minimally detectable, while cross-functional Fc-effector antibodies were present at higher baseline levels. The COVID-19 XBB.1.5 booster vaccination significantly boosted both neutralizing and Fc-effector antibodies in magnitude and breadth. The greatest increase in neutralizing antibodies was against the XBB.1.5 strain, while Fc-effector functional antibodies had similar fold-increases in antibody titers against the breadth of SARS-CoV-2 variants tested. Neutralizing and Fc-effector antibodies were most highly correlated at baseline (prior to booster vaccination) but were less correlated post-vaccination, consistent with differential boosting of neutralizing vs Fc-effector antibodies by the monovalent vaccine.ConclusionThe COVID-19 XBB.1.5 booster vaccination significantly improved the magnitude, breadth, and quality of antibody responses to SARS-CoV-2. Combining Fc-mediated functional and neutralizing antibody assays provides a more comprehensive model for understanding vaccine-induced immunity and optimizing vaccination strategies.